Secondary metabolites produced by endophytic bacteria against the Root-Knot Nematode (Meloidogyne sp.) - Vina Maulidia; Loekas Soesanto; Syamsuddin Syamsuddin; Khairan Khairan; Takahiro Hamaguchi; Koichi Hasegawa; Rina Sriwati (Society for Indonesian Biodiversity, 2020)
Abstract. Maulidia V, Soesanto L, Syamsuddin, Khairan K, Hamaguchi T, Hasegawa K, Sriwati R. 2020. Secondary metabolites produced by endophytic bacteria against the Root-Knot Nematode (Meloidogyne sp.). Biodiversitas 21: 5270-5275. Endophytic bacteria live and colonize in plant tissues without causing disease to their plant host. Among several processes, these bacteria can produce secondary metabolites that can help in the defense of plant host against pathogens. This study aimed to identify endophytic bacteria as biocontrol agents against Meloidogyne sp. in tomato plants. Six endophytic bacteria candidates from the genus Pseudomonas, Arthrobacter, Bacillus, and Serratia were isolated from Solanum Lycopersicum, Psidium guajava, Pinus merkusii, Dendrocalamus asper, Albizia chinensis, and Theobroma cacao L, respectively. The average mortality of Meloidogyne sp. by endophytic bacteria was 70,27% to 95,46%. From these, B. thuringiensis AK08 produced compounds of the secondary metabolites such as flavonoid, phenol, tannins, terpenoids, steroids, saponins, and alkaloids. The best result of the average incubation period, number of galls in the root, number of nematodes at the root, and the number of nematodes in the soil on tomato plant were shown by B. thuringiensis. The major compounds in GC-MS analysis of B. thuringiensis were cholest-5-en-3-ol (3.beta.)-carbonochloridate (25.35%). Bacillus thuringiensis not only has rules as bio-insecticide but also has nematicidal effect.